Rimpu Bima as a Basis for Internalising Religious Character in Primary Students - Rosmini; Fujiaturrahman, Sukron; Rezkillah, Inang Irma; Muhammad Hafeez; Garba, Malami Muhammad (Moestopo International Review on Social, Humanities, and Sciences, 2026)
Rimpu culture, as a reflection of the identity of the Bima community, contains religious values such as politeness, respect for women, and piety, making it relevant for character building in primary education. This study aims to identify the religious values embedded in the Rimpu tradition and analyse how these values are internalised in primary schools. Unlike previous studies that generally discuss character education based on local wisdom, this study specifically focuses on the formulation of the internalisation of religious values in the Rimpu tradition at the primary education level. This study uses qualitative ethnographic methods and was conducted in one of the primary schools in Bima Regency. Data were collected through participatory observation, in-depth interviews with traditional leaders, religious leaders, teachers, community members, and students, as well as documentation. Data analysis followed the Miles and Huberman model. The study shows that Rimpu religious values are reflected in community social practices and have begun to be applied in school activities. This study confirms that the Rimpu tradition can be positioned as a structured socio-religious value system with pedagogical significance in primary education.